Concepções de pedagogia universitária uma análise do Questionário de Avaliação do Ensino Ministrado na Universidade do Minho - Maria Melo do Céu; José Luís Silva; Álvaro Gomes; Flávia Vieira (Universidade do Minho, 2000)
The project Conceptions of University Pedagogy a Study in the University of Minho seeks to identify conceptions of pedagogy in this context, by focussing on instances of the official regulatory discourse and on the opinions of teachers and students from all the initial training courses. The authors present the results of the first stage of the project, by analysing an instrument used within this University since 1991, whereby students evaluate teaching, seeking to question its function, object and implications as a regulation tool. We conclude that the conception of pedagogy that underlies the questionnaire undermines its pedagogical value.